2021
DOI: 10.1177/09596518211028417
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydraulic proportional valve-controlled vane type semi-rotary actuated wind turbine control by feedforward fractional-order feedback controller

Abstract: In this study, proportional valve-controlled semi-rotary electrohydraulic actuator proposed for horizontal axis wind turbine pitch movement. Semi-rotary actuator can be connected directly to the wind turbine blade, which reduces mechanical complexity compare to linear electrohydraulic actuator system. Adaptive torque control scheme has been adopted for the horizontal axis wind turbine in region II; however, adaptive pitch control has been adopted for region III. Optimum pitch demand and torque demand have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…The lift force d F L and drag force d F D are experienced by the blade element due to wind flowing over it with velocity, V w . The resultant normal force d F N and the tangential force d F T can be obtained with relative wind angle, φ as follows 4,5…”
Section: Modeling Of the Semi-rotary Vane Type Eh Pitch Actuating Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…The lift force d F L and drag force d F D are experienced by the blade element due to wind flowing over it with velocity, V w . The resultant normal force d F N and the tangential force d F T can be obtained with relative wind angle, φ as follows 4,5…”
Section: Modeling Of the Semi-rotary Vane Type Eh Pitch Actuating Systemmentioning
confidence: 99%
“…The pressure in Chamber 1, P A and the pressure in Chamber 2, P B of the SRA can be obtained by neglecting the hydraulic oil compressibility effect, 4,37 and with pump pressure P P and tank pressure P T , given as…”
Section: Modeling Of the Semi-rotary Vane Type Eh Pitch Actuating Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Results showed that the compliance index of the new shield thrust system increased by 25% compared to that of existing one. Venkaiah et al [21] proposed a proportional valve-controlled semi-rotary electrohydraulic actuator for horizontal axis wind turbine pitch movement by feedforward fractional-order feedback controller. The proposed controller response has been compared with existing data of a 1.5 MW wind turbine.…”
Section: Introductionmentioning
confidence: 99%